PERLINDUNGAN HUKUM BAGI TENAGA KERJA INDONESIA DARI TINDAK PIDANA PERDAGANGAN ORANG (Studi Kasus Putusan Nomor 31/Pid.Sus/2016/PN.Kfm) - Fadhiil Ali Hakim, - (2019)
Human Trafficking is the act of recruiting, transporting, dispatching, shipping, transferring or receiving someone who is threatened with violence, use of violence, abduction, confinement, fraud, abuse of power or vulnerable position, debt trapping or paying or benefits so as to obtain approval from the person take control of the benefits so that they get the approval of the person who has control over the other person, whether done within the country or between countries, for the purpose of exploitation or causing the person to be exploited. The practice of trafficking in the conventional sense is most visible in afflicting children and prostituted women. However, there is actually a practice that fulfills all elements of the definition in the term trade in people who use Indonesian labor as victims. The research used in this paper is a lebal normative research method, this study is also to determine the criminal liability of perpetrators of the Crime of Human Trafficking against Indonesian Workers who are victims. knowing the efforts to combat Human Trafficking who use Indonesian labor. The results of the research of most shipments of Indonesian Workers, especially from 2010 to 2015, are colored by a number of violations of law that are included in the crime of human tracfficking. Criminal acts are carried out covertly with labels or the sending of candidates for Indonesian Workers or Indonesian Workers. This is done by the perpetrators solely to obtain economic benefits.